An empirical study of direct relationship of service quality, customer satisfaction and customer trust on customer loyalty in Malaysian rural tourism / Zahir Osman - Osman, Zahir (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA (UiTM), Malaysia, 2013)
The purpose of this study is to develop a direct effect understanding of service quality, customer satisfaction and trust on customer loyalty in Malaysia rural tourism. The Structural Equation Model (SEM) used to analyze the casual relationships between independent variables and dependent variable. The model was developed and later tested by adopting the Partial Least Square (PLS) procedure on data collected from a survey that yielded 295 usable questionnaires. The findings showed that service quality, customer satisfaction and trust have significant and positive influence on customer loyalty in Malaysia rural tourism. It is important to do the study utilizing experimental design by capturing longitudinal data in Malaysia rural tourism industry using robust measures. The findings imply that the relationship of service quality, satisfaction and trust on customer loyalty will lead to rural tourism operators' profitability. This research is one of the first known attempts to use PLS to test a direct effect